Quality of Omnichannel Integration and Perceived Value as Drivers of Customer Satisfaction and Loyalty Study at BNI Bank - Nabila, Nuzul Inas; Sari, Aida; Marvinita, Risda; Vedy, Hanifa Syahirah (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2023)
This study investigates the relationship that exists between omnichannel integration quality, customer value and customer responsiveness, namely satisfaction and loyalty. This research was conducted at Bank BNI. More specifically, this research aims to evaluate whether the positive value created by the omnichannel system as perceived by customers and a higher level of integration quality (integrity quality) can be one of the important drivers of bank customer satisfaction and loyalty. The method used for this study is a quantitative method, which involves parameter estimation, hypothesis testing, establishing confidence intervals, and the relationship between two or more characteristics (variables) for parameters with a known distribution (normal distribution). Next, it was analyzed using validity and reliability and PLS hypothesis testing. The unit of analysis in this research was 148 BNI bank customers. The results of this study include the following: There is a significant relationship between the quality of omnichannel integration and perceived value at Bank BNI, there is a significant relationship between the quality of omnichannel integrity and customer satisfaction at BNI Bank, there is a significant relationship between omnichannel perceived value (perceived value) on customer satisfaction at bank BNI, there is no significant effect between the quality of omnichannel integration on customer loyalty at Bank BNI, there is a significant effect between the omnichannel perceived value on customer loyalty at Bank BNI, there is an influence significant relationship between satisfaction and customer loyalty at Bank BNI.